Analisis Rasio Aktivitas Untuk Mengukur Kinerja Keuangan PT PLN Persero Periode 2021 – 2023 - Rika Regita Cahyani; Haqi Insani; Eva Sriwiyanti (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
Problems related to finance are very crucial problems for an entity, so it is necessary to carry out an analysis of its financial reports. The target of this research is to analyze activity ratios in order to measure the financial performance of PT PLN (Persero) during the 2021-2023 period. The approach used is a quantitative descriptive method. The research results show that the billing turnover ratio in the 2021-2023 period has decreased but is still in the Healthy category. Analysis of the inventory turnover ratio in the 2021-2023 period has decreased, however the company is still in the Healthy category. Analysis of the total asset turnover ratio for the 2021-2023 period has increased. Even though it has increased, the company is in the Less Healthy category. We hope that the research results can provide an in-depth understanding regarding the financial stability of PT PLN (Persero) and become a consideration in making the right decisions.